2004
DOI: 10.1897/03-456
|View full text |Cite
|
Sign up to set email alerts
|

Association of heavy metals with metallothionein and other proteins in hepatic cytosol of marine mammals and seabirds

Abstract: Distribution of Cu, Zn, Cd, Ag, Hg, and Se were determined in hepatocytosol of northern fur seals (Callorhinus ursinus), black-footed albatrosses (Diomedea nigripes), and Dall's porpoises (Phocoenoides dalli). Copper, Zn, and Cd were accumulated preferentially in metallothionein (MT) fraction and their contents in MT fraction increased with the amounts in the hepatocytosol. Silver was bound to both high-molecular-weight substances (HMWS) and MT in the hepatocytosol for all three species, whereas the distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 80 publications
3
32
1
Order By: Relevance
“…In the second approach, it is assumed that dissociation or ligand exchange does occur in biota and that elimination of the organotin cation is similar to metal elimination kinetics as metals bind to proteins as well. An important metalbinding protein in animals is metallothionein (Ikemoto et al, 2004). This binding to proteins is incorporated in OMEGA as a generic dry tissue-water distribution coefficient (K tw ), which results in a lower elimination rate compared to hydrophobic organic substances.…”
Section: Uptake and Eliminationmentioning
confidence: 99%
“…In the second approach, it is assumed that dissociation or ligand exchange does occur in biota and that elimination of the organotin cation is similar to metal elimination kinetics as metals bind to proteins as well. An important metalbinding protein in animals is metallothionein (Ikemoto et al, 2004). This binding to proteins is incorporated in OMEGA as a generic dry tissue-water distribution coefficient (K tw ), which results in a lower elimination rate compared to hydrophobic organic substances.…”
Section: Uptake and Eliminationmentioning
confidence: 99%
“…It has been shown that various vertebrates are able to detoxify Hg by a specific chemical mechanism involving Se, suggesting that Se has an antagonistic effect on Hg metabolism (Elia et al, 2003;Ikemoto et al, 2004;Kunito et al, 2004). This relation has also been documented in marine ecosystem (Dietz et al, 2000;Campbell et al, 2005;Kehrig et al, 2009b).…”
Section: Trophic Transfer Of Trace Elementsmentioning
confidence: 79%
“…In several studies, the ratio between Hg and Se molar concentrations was close to equimolarity in marine mammals and birds, but a large excess of Se in relation to Hg was observed in fishes and crustaceans (Andersen and Depledge, 1997;Dietz et al, 2000;Ikemoto et al, 2004;Kunito et al, 2004;Campbell et al, 2005;Kehrig et al, 2009b). It has been shown that various vertebrates are able to detoxify Hg by a specific chemical mechanism involving Se, suggesting that Se has an antagonistic effect on Hg metabolism (Elia et al, 2003;Ikemoto et al, 2004;Kunito et al, 2004).…”
Section: Trophic Transfer Of Trace Elementsmentioning
confidence: 99%
“…In terrestrial mammals, such as rats and mice, binding of Hg to MT has been demonstrated and induction of these proteins after Hg exposure (Morcillo and Santamaria, 1993;García-Sevillano et al, 2015;Orct et al, 2015). However, the role of MT in the detoxification of Hg is controversial; studies in marine mammals have indicated that a small percentage of Hg is bound to MT in liver and kidney (Decataldo et al, 2004;Ikemoto et al, 2004aIkemoto et al, , 2004b. All specimens analyzed here had Hg concentrations below the tolerance limit for cetaceans (100-400 mg·kg −1 w.w. liver, Wagemann and Muir, 1984), and therefore, the Hg concentrations were likely not high enough to induce the synthesis of MT.…”
mentioning
confidence: 79%